Construction of a density mutant collection in bitter gourd via new germplasms innovation and gene functional study - Yu, Renbo; Niu, Yu; Wang, Xiaoyi; Yang, Kaili; Han, Xu; Liu, Zhaohua; Qi, Zhiqiang; Yang, Yan (Frontiers in Plant Science, 2022)
Although a few studies have elucidated the creation of bitter gourd mutants, the suitable concentration and duration of ethyl methanesulfonate (EMS) mutagenesis have not been determined. In this study, mutant collection was conducted to create new germplasms and widen genetic diversity. By employing the seeds of the inbred line Y52 as the mutagenic material, ethyl methanesulfonate (EMS) as the mutagen, and the suitable mutagenic conditions for bitter gourd seeds (EMS concentration 0.2 %, mutagenic time 10 h), we mutated 10000 seeds and acquired 3223 independent M2 lines. For the randomly selected 1000 M2 lines, 199 M2 lines with visible phenotypes were found, and 167 M2 lines were mutants of fruit shape, size, and tubercles. Furthermore, 14 dwarf, 11 leaf color, five leaf shape, and eight meristem defect mutants were discovered in this mutant collection. In addition, three lines of 1253, 2284, and 3269 represented recessive mutants crossed with Y52. Furthermore, the yellow leaf lines of 2284 and 3269 were not mutated at the same gene locus. This study constructed a mutant collection through innovative new germplasms and provided valuable resources for bitter gourd breeding and functional gene research.